Генетическое расщепление в семенном потомстве при митотической агамоспермии - Левитес, Е.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. The previously published data are examined on the base of the hypothesis about the existence of chromosomes differential polyteny and excessive chromatin diminution during the first stages of sugar beet plant embryogenesis. Conclusions. It has been concluded that available data provide the genetic proof of that chromatin diminution is one of the mechanisms underlying the origin of polymorphism in sugar beet progenies under mitotic agamospermy.

Key words: isozymes, polyteny, diminution, agamospermy, non-Mendelian inheritance, sugar beet.